Pengaruh Padat Tebar Terhadap Prevalensi Penyakit EHP (Enterocytozoon Hepatopenaei) Pada Udang Vaname (Litopenaeus Vannamei) Mulai PL8-DOC40 di Bak-Bak Percobaan - Maulida Salsabila Chudlori; Muhajir Muhajir; Sumaryam Sumaryam (Dinasti Research, 2024)
Intensive shrimp farms sometimes experience cases of death of vaname shrimp (Litopenaeus vannamei) due to infection with various pathogens and one of these diseases is EHP (Enterocytozoon Hepatopenaei). This disease mostly attacks vaname shrimp in the post-lava phase, EHP can take up nutrients in the digestive tract so that it can inhibit growth, non-uniform size variations and be deadly. EHP can also become a primary infection and open the way for other disease. This research used an experimental method with a Completely Randomized Design (CRD) consisting of 5 treatments with 5 replications. The results showed that treatment A gave the best results for the prevalence of EHP disease in white shrimp (Litopenaeus vannamei) from PL8–DOC40 at 7%. Water quality data obtained from water temperature ranged from 27.1 to 29.9 0C, acidity ranged from 7.1 to 8.6 and dissolved oxygen ranged from 5.14 to 5.87 ppm.